Adaptations to High Salt in a Halophilic Protist: Differential Expression and Gene Acquisitions through Duplications and Gene Transfers - Harding, Tommy; Roger, Andrew J.; Simpson, Alastair G. B. (Frontiers in Microbiology, 2017)
The capacity of halophiles to thrive in extreme hypersaline habitats derives partly from the tight regulation of ion homeostasis, the salt-dependent adjustment of plasma membrane fluidity, and the increased capability to manage oxidative stress. Halophilic bacteria and archaea have been intensively studied, and substantial research has been conducted on halophilic fungi, and the green alga Dunaliella. By contrast, there have been very few investigations of halophiles that are phagotrophic protists, i.e. protozoa. To gather fundamental knowledge about salt adaptation in these organisms, we studied the transcriptome-level response of Halocafeteria seosinensis (Stramenopiles) grown under contrasting salinities. We provided further evolutionary context to our analysis by identifying genes that underwent recent duplications. Genes that were highly responsive to salinity variations were involved in stress response (e.g. chaperones), ion homeostasis (e.g. Na+/H+ transporter), metabolism and transport of lipids (e.g. sterol biosynthetic genes), carbohydrate metabolism (e.g. glycosidases), and signal transduction pathways (e.g. transcription factors). A significantly high proportion (43%) of duplicated genes were also differentially expressed, accentuating the importance of gene expansion in adaptation by H. seosinensis to high salt environments. Furthermore, we found two genes that were lateral acquisitions from bacteria, and were also highly up-regulated and highly expressed at high salt, suggesting that this evolutionary mechanism could also have facilitated adaptation to high salt. We propose that a transition toward high-salt adaptation in the ancestors of H. seosinensis required the acquisition of new genes via duplication, and some lateral gene transfers, as well as the alteration of transcriptional programs leading to increased stress resistance, proper establishment of ion gradients, and modification of cell structure properties like membrane fluidity.